Perilaku pencarian informasi pengunjung terkait user education di Perpustakaan Kota Bogor - Zulfa Syakirah; Malyda Safira Azahra; Irdan Hildansyah; Resa Restu Pauji (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
User education refers to the dissemination of knowledge carried out by libraries to their users. This knowledge includes how to develop skills in utilizing library facilities, how to use available services, and other relevant information that can assist users during their visit to the library. This study aims to suggest effective methods for librarians and library staff to disseminate user education information so that it can be directly implemented. Additionally, the study describes how users obtain information related to user education in order to identify their information-seeking behavior. This research employs a qualitative descriptive approach with data collected through interviews with librarians, library staff, and visitors, as well as observations at Perpustakaan Kota Bogor. The results of this study indicate that user information-seeking behavior is passive and dependent on officers, even though information related to user education is available. The irregularity of information and weak direction make it difficult for users to navigate services independently. Therefore, a more comprehensive and sustainable education strategy is needed so that users can search for information more optimally